2011
DOI: 10.1002/pola.24732
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐free synthesis of novel biobased dihydroxyl‐terminated aliphatic polyesters as building blocks for thermoplastic polyurethanes

Abstract: Using the organic compound 1,5,7‐triazabicyclo[4.4.0]dec‐5‐ene (TBD) as a catalyst for step‐growth polymerization, a series of well‐defined hydroxyl‐telechelic renewable aliphatic polyesters (including poly(1,3‐propylene adipate); poly(1,4‐butylene adipate); poly(1,12‐dodecylene sebacate); and poly(1,2‐dimethylethylene adipate), PDMEA) were synthesized and studied. PDMEA is a novel polyester, which has not been reported before. The results of 1H NMR and Matrix‐assisted laser desorption ionization time‐of‐fligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 33 publications
(39 reference statements)
5
32
0
Order By: Relevance
“…The results are shown in Figure 1 and Table 2, from which it is observed that all the TPUUs exhibit similar degradation behavior as a function of the temperature, with the exception of 4U PDMES and 3U PDMES . These two PDMES‐based polymers are less stable than the other polymers, which fits the trend of the relatively poor thermal stability of PDMES described previously 19. As shown in Table 2, the thermal stability of the TPUUs doesnot significantly depend on the different lengths of the HSs.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The results are shown in Figure 1 and Table 2, from which it is observed that all the TPUUs exhibit similar degradation behavior as a function of the temperature, with the exception of 4U PDMES and 3U PDMES . These two PDMES‐based polymers are less stable than the other polymers, which fits the trend of the relatively poor thermal stability of PDMES described previously 19. As shown in Table 2, the thermal stability of the TPUUs doesnot significantly depend on the different lengths of the HSs.…”
Section: Resultssupporting
confidence: 83%
“…The polyester diols, including poly(1,4‐butylene adipate) (PBA), poly(1,2‐dimethylethylene adipate) (PDMEA) and poly(1,2‐dimethylethylene succinate) (PDMES), were prepared in house (details of their preparation are described in a previous publication19 and their molecular weights are given in Table 1). Poly(1,2‐propylene glycol) (PPG, M n = 725 g mol −1 ), hexamethylene diisocyanate (HDI, > 99.0%), 1,6‐diaminohexane (DAH, 98%), dibutyltin dilaurate (DBTDL), phosphate‐buffered saline (PBS, pH 7.4), and pseudomonas cepacia Lipase (Lipase PS) were purchased from Sigma–Aldrich.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using this strategy, Koning and coll. have prepared partially fatty acidbased aliphatic polyester diols from dimethyl sebacate using TBD as a catalyst (Tang et al, 2011). Moreover, Corcuera and coll.…”
Section: Diols Containing Ether and Ester Functionsmentioning
confidence: 99%
“…A pTHF to diisocyanate ratio of 2 to 3 was chosen to obtain a doubling in molecular weight. 28 The prepolymer was analyzed via SEC and the isocyanate content was determined via titration. The SEC trace of the prepolymer, confirming the increase in molar mass, is presented in Figure S1 of the Supporting Information section and is compared with the SEC elugram of the initial pTHF.…”
mentioning
confidence: 99%